Paranoia in adolescents: assessment, prevalence, and clinical understanding - Bird, J (2020)
Background Adolescence is the age when paranoia is most likely to first arise. Believing that others intend to harm you is likely to be corrosive for social relationships; this, in turn, could worsen outcomes for young people with mental health disorders. To date, however, paranoia has been predominantly studied in adults. Very little is known about its clinical presentation in adolescents. In this thesis, a systematic programme of research examining paranoia in adolescents - particularly those in clinical services - was conducted. The aims were to 1) develop an age-appropriate assessment of paranoia for young people, 2) establish the extent to which paranoia is a problem in adolescents attending mental health services, and 3) improve the clinical and theoretical understanding of paranoia at this age.